The jasmonoyl‐isoleucine receptor CORONATINE INSENSITIVE1 suppresses defense gene expression in Arabidopsis roots independently of its ligand. (22nd July 2021) - Ulrich, Louisa; Schmitz, Johanna; Thurow, Corinna; Gatz, Christiane
Summary: The F‐box protein CORONANTINE INSENSITIVE1 (COI1) serves as the receptor for the plant hormone jasmonoyl‐isoleucine (JA‐Ile). COI1, its co‐receptors of the JASMONATE ZIM‐domain (JAZ) protein family, and JA‐Ile form a functional unit that regulates growth or defense mechanisms in response to various stress cues. Strikingly, COI1, but not JA‐Ile, is required for susceptibility of Arabidopsis thaliana towards the soil‐borne vascular pathogen Verticillium longisporum . In order to obtain marker genes for further analysis of this JA‐Ile‐independent COI1 function, transcriptome analysis of roots of coi1 and allene oxide synthase ( aos ) plants (impaired in JA biosynthesis) was performed. Intriguingly, nearly all of the genes that are differentially expressed in coi1 versus aos and wild type are constitutively more highly expressed in coi1 . To support our notion that COI1 acts independently of its known downstream signaling components, coi1 plants were complemented with a COI1 variant (COI1AA ) that is compromised in its interaction with JAZs. As expected, these plants showed only weak induction of the expression of the JA‐Ile marker gene VEGETATIVE STORAGE PROTEIN2 after wounding and remained sterile. On the other hand, genes affected by COI1 but not by JA‐Ile were still strongly repressed by COI1AA . We suggest that COI1 has a potential moonlighting function that serves to repress gene expression in a JA‐Ile‐ and JAZ‐independent manner. Significance Statement: Phenotypic differences of hormone receptor and corresponding hormone biosynthesis mutants are unexpected. Such an unusual scenario was discovered for COI1, which affects the root transcriptome even when disconnected from its signaling pathway.